THE EFFECT OF MERGERS AND ACQUISITIONS ON THE CAPITAL STRUCTURE OF COMPANIES IN ISLAMIC PERSPECTIVE IN SHARIA BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017 – 2021 PERIOD: English - mohamad faisal; Tulasmi (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
This study aims to determine the analysis of the effect of mergers and acquisitions of companies on the company's capital structure in an Islamic perspective in Islamic banking companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study are Islamic banking companies listed on the Indonesia Stock Exchange for the period 2017-2021. Sampling in this study was conducted by purposive sampling method. The criteria for companies that are used as research samples are Islamic banking companies that have gone public and are listed on the Indonesia Stock Exchange during the research period, namely 2017-2021, the availability of information on the financial statements of Islamic banking companies during the research period. Research samples that meet the criteria are taken as many as 3 go public sharia banking companies that are listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses multiple linear regression analysis to test whether capital structure is influenced by various variables, namely Fixed Asset Ratio (FAR), Growth Sales (GS), Firm Size (SIZE), Return On Equity (ROE), Degree of Financial Leverage (DFL). ), and Dividend Payout Ratio (DPR). The results of this study partially are Fixed Asset Ratio, Firm Size, Return On Equity, and Degree of Financial Leverage have a significant effect on the Debt to Equity Ratio. Meanwhile, Sales Growth and Dividend Payout Ratio have no partial significant effect on the Debt to Equity Ratio. Based on the results of the statistical f test, it shows that the Fixed Asset Ratio, Growth Sales, Firm Size, Return On Equity, Degree of Financial Leverage, and Dividend Payout Ratio variables simultaneously affect the Debt to Equity Ratio in Islamic banking companies that have gone public and are listed on the Stock Exchange. Indonesian Securities in 2017-2021.